Experimental studies on the operation of agricultural crops mowing unit with simultaneous chopping and incorporation of stubble into the soil. - Nadykto, Volodymyr; Kiurchev, Sergey; Chorna, Tatiana; Hutsol, Taras; Mudryk, Krzysztof; Głowacki, Szymon; Rud, Anatoliy; Shevtsova, Alona; Ryabov, Igor; Szwedziak, Katarzyna; Надикто, Володимир Трохимович; Кюрчев, Сергій Володимирович (My University, 2023)
For harvesting crops, one-phase and two-phase methods are most often used. When implementing the second one, mounted and trailed units are used. The latter is becoming less and less used due to the problems with movement stability in the horizontal plane because of the asymmetric layout. A stubble background, which is susceptible to solar and wind influences, is formed as a consequence of appli- cation of the mounted harvesting unit, As a result, the field's soil in the inter-swath space intensively loses moisture. A harvesting unit based on a tractor with rear steerable wheels has been designed to eliminate this shortcoming. A header is mounted on its front hitch linkage system, and a disc harrow is mounted on the rear one. During the working movement, such a harvesting unit mows the crop into swaths, chops the stubble in the inter-swath space, and simultaneously incor- porates it into the soil. This article presents the operation results of such a unit for harvesting winter wheat, oats, and sudan grass. Research has established that os- cillations in the deviations of the mowed crops' swaths from a straight line are of low frequency. The variances spectra of this process, as follows from the Analysis of normalized spectral densities, are concentrated in the frequency range of 0-0.5 m-1. The mean value velocities of the harvesting unit are 2.13-2.61 m·s-1, which is 0.17-0.21 Hz. The variances of oscillations in the header operating width, the cut crop's swath width, and the disc harrow's width are concentrated in approxi- mately the same low-frequency range, the maximum value of which is small and does not exceed 0.9 m-1 or 0.37 Hz. The oscillation processes of the mowed crops' stubble height have a higher frequency. The cutoff frequency of their normalized spectral densities is at the level of 3.0 m-1. In terms of time, considering the har- vesting unit movement velocity of 2.13-2.61 m⋅s-1, this is 1.02-1.25 Hz. At the same time, oscillations in the stubble height of mowed crops are characterized by small variances, the maximum value of which does not exceed 11 cm2.
Keywords: header; disc harrow; swath; stubble height